Expression of the sweat‐derived innate defence antimicrobial peptide dermcidin is not impaired in Staphylococcus aureus colonization or recurrent skin infections. (20th June 2013) - Rieg, S.; Saborowski, V.; Kern, W. V.; Jonas, D.; Bruckner‐Tuderman, L.; Hofmann, S. C.
Summary Antimicrobial peptides are an integral part of innate immunity, and contribute to the protection of human skin from Staphylococcus aureus colonization and infection. We sought to investigate whether the expression of the eccrine sweat‐derived staphylocidal antimicrobial peptide dermcidin might influence S. aureus colonization or recurrent skin and soft‐tissue infections (SSTIs). Eccrine sweat was collected from 18 patients with recurrent S. aureus SSTIs, 28 patients who were intermittent or permanent S. aureus carriers, and 32 noncarriers. Expression and proteolytic degradation of dermcidin was investigated using ELISA and surface‐enhanced laser desorption ionization time‐of‐flight mass spectrometry (SELDI‐TOF‐MS). We found no significant differences in the overall amount or the proteolytic degradation pattern of dermcidin‐derived peptides between healthy noncarriers, intermittent and permanent carriers, and patients with recurrent S. aureus SSTIs. S. aureus colonization or recurrent SSTIs do not seem to be associated with diminished dermcidin expression in eccrine sweat.